Tacito venetai = vakarų baltai? Faktai ir hipotezės - Laučiūtė, Jūratė Sofija (Baltistica, 2009)
ARE THE VENETHI OF TACITUS SYNONYMOUS WITH WESTERN BALTS? Veneti (Lat. Venedi, Venethi; Gr. Ουενέδαι) usually describes a tribe or confederation of tribes which are mentioned by many antique and modern historians and geographers. This article addresses those Veneti about whom the historian and political figure of the Roman Empire, Publius Cornelius Tacitus, wrote in his work Germania (‘De origine et situ Germanorum’, 98 AD). The ethnic identity of this tribe has given birth to many hypotheses, one of which associates the Veneti of Tacitus with the Baltic tribes. The first part of the article brings together the most important facts on the distribution of the name Veneti, beginning with the oldest data reaching back before the Christian era and concluding with the latest information from the 20th century. The second part presents onomastic material, which in one form or another reflects the root (stem) ven-/ven-t/ven-et-, and upon which hypotheses on the ethnic affiliation of the Veneti are usually based. The third part analyzes the most frequently discussed hypotheses, with attention paid to the distinction of ethnic-linguistic elements of Baltic ethnic origin from the Slavic ones. Based on the facts presented, two problems are elucidated and discussed. 1. The origin of the Veneti tribe itself and its ethnic affiliation: who were Tacitus’ Veneti? 2. The etymology of the name Veneti.